The Effect of Asta Brata Leadership and Organizational Culture on Employee Commitment Through Job Satisfaction at The Pratama Sidhi Sai Clinic Badung Bali - Dian Efriliana; Yeyen Komalasari; R Tri Priyono Budi Santoso; I Wayan Ruspendi Junaedi (UPT Jurnal & Publikasi Ilmiah SPs Universitas Ibn Khaldun Bogor, 2026)
This study aims to analyze the influence of Asta Brata leadership and organizational culture on employee commitment with job satisfaction as a mediating variable at Klinik Pratama Sidhi Sai, Bali. Using a quantitative explanatory design, data were collected through questionnaires administered to all employees and analyzed using Structural Equation Modeling–Partial Least Squares (SEM–PLS). The results show that Asta Brata leadership has a significant positive effect on job satisfaction and employee commitment, while organizational culture significantly affects job satisfaction but does not directly influence commitment. Job satisfaction strongly affects employee commitment and mediates the relationship between leadership and commitment (partial mediation) as well as between organizational culture and commitment (full mediation). The research model explains 87% of the variance in job satisfaction and 93.2% of the variance in employee commitment. These findings emphasize that local wisdom–based leadership and a supportive organizational culture enhance employee commitment primarily through increased job satisfaction, offering strategic implications for strengthening loyalty, satisfaction, and service quality in healthcare institutions.